The Role Of The Special Child Development Institution (Lpka) In Providing Guidance To Children Who Are In Conflict With The Law As An Effort To Prevent The Repetition Of Criminal Acts (Study At Lpka Class I Medan) - Albert Septiman Berkat Halawa; Herlina Manullang; Ojak Nainggolan (PALAR | PAKUAN LAW REVIEW, 2026)
The Child Special Development Institution (LPKA) has an important role in providing guidance for children in conflict with the law as an effort to prevent the repetition of criminal acts (recidivism). This study aims to analyze the role of the Child Special Development Institution (LPKA) in conducting guidance for children in conflict with the law and to identify the obstacles faced in the implementation of such guidance at LPKA Class I Medan. This research uses an empirical juridical approach with a qualitative method. Data were obtained through interviews, observations, and literature studies related to the implementation of guidance programs for children at LPKA Class I Medan. The results of this study show that LPKA plays a significant role in the development of children through various programs such as personality development, education, vocational skills training, religious guidance, and social reintegration programs. These programs aim to improve the behavior and mentality of children so that they are able to reintegrate into society and avoid repeating criminal acts. However, in its implementation there are several obstacles, including limited facilities and infrastructure, a shortage of professional human resources, and the diverse backgrounds of the children. Therefore, improvements in facilities, infrastructure, and institutional capacity are necessary to optimize the guidance process.   Keywords: hild Special Development Institution (LPKA), children in conflict with the law, guidance, recidivism prevention, criminal acts.